Most Common Learning Style Used by the Students of English Department of Tidar University - Riadil, Ikrar Genidal; Nur, Muhammad Rauuf Oktavian (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2019)
To make a good classroom environment as students’ stimulation, that will make the students active in the teaching and learning process. Understanding the students’ learning styles helps the teacher to teach about the student’s specific favorites. Understand the kind of learning styles can help the teacher developing and also delivering the educational programs. It also will motivate and stimulate students’ in gaining the knowledge. This research pursues to answer two research questions; (1) To know the kind of learning styles used by the students of English Department of Tidar University. (2) To know about the most common learning style used by the students of English Department of Tidar University. Qualitative research is used in this research. This research aims to distinguish the most common used of learning style and used the questionnaire reproduced by O’Brien (1985). The population of this research was the English Department students of Tidar University. However, the researcher used 70 samples from all of the students of English Department of Tidar University.